Silver-Loaded Chabazite in Ethanol-to-Hydrocarbon Process—Operando FT-IR and UV-Vis Spectroscopic Studies - Karolina A. Tarach; Anna K. Walczyk; Agata Kordek; Oliwia Rogala; Kinga Góra-Marek (Molecules, 2024)
The ethanol dehydration process is studied regarding protonic and Ag-loaded chabazite zeolite in advanced FT-IR and UV-vis operando spectroscopic studies with simultaneous mass spectroscopy and gas chromatography analyses of products. The spectroscopic investigation provides information on the species formed on the surface of catalysts, while mass spectrometry and gas chromatography methods identify the desorbed products. These studies are also supported by spectroscopic, chromatographic, and thermogravimetric analyses of coke species formed over the catalyst’s surface during ethanol conversion. The Ag-chabazite catalyst shows higher selectivity for ethylene and propylene; the slower formation of coke species; and, thus, a longer lifetime.